The Impact of Social Media Influencers on Consumer Brand Awareness and Consumer Perceived Quality towards Brand Image - He, Shu Kun (2022)
In recent years, due to the development of information technology, many social media platforms such as Facebook, Instagram, YouTube have been transformed from the past function of simply providing entertainment to the public into the most effective advertising medium. Due to the high number of Internet users in Malaysia, it is very common for businesses to deliver advertisements through social media. Among them, social media influencer is one of the new occupations that have emerged under this trend. Social media influencers create entertaining content for the masses they follow, as well as creating ad-valued views. In view of this situation, it is very important for brand building to have a deep understanding of how the factors that affect the advertisements delivered by the browsing merchants on social media through the influencer will affect the audience. This study mainly explores how the feelings presented by the personal characteristics of social media influencers in Malaysia affect the audience's perception of advertising products and the effect of brand image building. This study uses quantitative research to investigate the relationship between social media influencers, brand awareness, perceived quality, and brand image. The results show that social media influencers have a positive and significant effect on brand awareness and perceived quality; perceived quality has a positive and significant effect on brand image; brand awareness has no significant statistical level on brand image. The perceived quality has a mediating effect between social media influencer and brand image. It is shown that when using social media influencers to advertise products, the perceived quality will be an important factor for the effect of advertising and brand image establishment.